Who has the time? A qualitative assessment of gendered intrahousehold labor allocation, time use and time poverty in rural Senegal - Marter-Kenyon, Jessica Susan; Blakeley, S. Lucille; Banks, Jacqueline Lea; Ndiaye, Codou; Diop, Maimouna (Frontiers in Sustainable Food Systems, 2023)
Achieving gender equality in agricultural development is fundamental to reductions in global poverty, hunger and malnutrition. African women make important contributions to farming and food systems; however, their efforts are often hindered by inefficient and inequitable allocations of intrahousehold labor and time that render women time poor. Time poverty is a root cause of women’s marginalization in rural Africa and an important area of inquiry for feminist scholarship. While gendered time use and time poverty have been researched in many different contexts and countries in Africa, significant knowledge gaps remain. Most studies consider women’s time use divorced from gendered relations, and overlook children’s contributions. Other factors which may combine to influence women’s time burden but are often overlooked include seasonality, work intensity, household structure and composition, cultural norms, familial relationships and intrahousehold power dynamics. Further, the majority of research on gendered time use and time poverty in Africa uses quantitative methods applied to secondary data, which presents challenges for critically identifying and characterizing the confluence of various intrahousehold dynamics which impact women’s multiple roles, responsibilities, and consequently their work and time. This study adds important nuance to the existing body of research by offering an in-depth, qualitative assessment of intrahousehold labor allocation, time use, and time poverty amongst women, men, and children living in multi-generational, largely polygamous households reliant on peanut-farming in the Kaolack region of Senegal. Data collection took place in February 2020, with 111 individuals in three villages. We find that individual workload correlates with gender and age, but is further determined by the demographic composition of the household, the roles assumed by the individual and other family members, and the individual’s place within the social hierarchy. Women and girls in Kaolack are clearly at more risk of time poverty due to their dual responsibility for reproductive and productive work, especially during the rainy season. Furthermore, women’s workload in particular changes over the life course as they assume different roles in different life stages. As a result, women with older daughters and, especially, daughters-in-law are significantly less time poor than other women.